Modification of Surface Buoy to Preserve Under Water Habitat in Raja Ampat - Ocid Mursid; Nurul Huda; Haris Nubli (Department of Naval Architecture - Diponegoro University, 2022)
The ecosystem of the seabed is threatened by anchoring operations. Modifications were required toreduce the damage to seabed biodiversity. A laid chain on a mooring system is one of the causes ofdamage to the seabed environment. In this paper, six mooring configurations are studied to achieve theoptimum configuration on the moored vessel KM Putri Mandiri based on the chain length laid, thetension chain, and the vessel offset. The benefit of this study is to preserve the underwater habitat in RajaAmpat. The quantities and buoyancy capacities of the surface buoy are used as variable designs in thisstudy. Ansys Aqwa software is utilized to calculate mooring systems with environmental conditions,water depth 15 m, wave height 1.5 m, wind velocity 15 knots, and sea current speed of 1 m/s. The resultsshowed that more surface buoys caused lower laid chain length and closer ship offset but increasedtension chain. Configuration E, which consists of 3 surface buoys, was the optimum configuration for thisstudy.